(untitled) (Law and world, 2020)
The decision of the High Court of Australia in Neilson is a very rare event, since it contains an extended consideration of renvoi by a national court of final appeal in a case containing a real renvoi issue. Not surprisingly, the case attracted considerable interest among private international lawyers around the world even before it reached the Court, and the Court’s decision was eagerly awaited.